Enhancing reading literacy among elementary school learners in Kazakhstan: The application and effectiveness of modern teaching techniques - Abildina, S.; Sarsekeyeva, Zh.; Mukhametzhanova, A.; Kopbalina, K.; Nurgaliyeva, S. (Journal of Infrastructure, Policy and Development, 2024)
This study investigates the application and effectiveness of modern teaching techniques in improving reading literacy among elementary school students in Kazakhstan. In the rapidly evolving educational landscape, the integration of innovative pedagogical strategies is essential to foster student reading skills and general literacy. This study aims to explore how these modern teaching techniques can be applied to improve reading literacy among elementary school students in Kazakhstan. The study sample includes 64 respondents to the research. The key modern teaching techniques explored in this study include the use of digital learning tools, interactive reading sessions, differentiated instruction, and collaborative learning activities. The findings reveal significant improvements in reading literacy among students exposed to these techniques, highlighting the potential of modern pedagogy to bridge literacy gaps and promote educational equity. Furthermore, the study discusses the challenges and opportunities to implement these techniques within the Kazakhstani educational system. The results provide valuable information for educators, policymakers, and stakeholders aiming to improve reading literacy through innovative teaching practices
Keywords: effectiveness; enhancing; elementary school; learning; modern teaching techniques